Urban-rural consumption inequality in China from 1988 to 2002: evidence from quantile regression decomposition - Zhaopeng Qu; Zhong Zhao (Institute for the Study of Labor (IZA), 2008)
One of the most notable social phenomena in China is the large urban-rural disparity. There are many studies of it, but most of them focus on income or earnings inequality. In this paper, we investigate the consumption disparity between urban and rural households in China from 1988 to 2002. Our results suggest that low quantiles are associated with large consumption disparity. The price effect is the dominant factor for the urban-rural consumption disparity. This disparity increased significantly, both at mean and at every quantile, from 1988 to 2002. However, most of the increase happened from 1988 to 1995, and this increase was mainly from the higher growth rate of urban household consumption. Our results also suggest that rural-urban migration and improvement of the rural educational level are very helpful in reducing urban-rural disparity.
urn:nbn:de:101:1-20080828323
Keywords: O18; 330; Inequality; consumption; quantile regression decomposition; China; Gesamtwirtschaftlicher Konsum; Regionale Disparität; Stadt-Land-Beziehung; Ländlicher Raum; China